Adipose tissue macrophages: going off track during obesity - Boutens, Lily (Diabetologia, 2016)
Inflammation originating from the adipose tissue is considered to be one of the main driving forces for the development of insulin resistance and type 2 diabetes in obese individuals. Although a plethora of different immune cells shapes adipose tissue inflammation, this review is specifically focused on the contribution of macrophages that reside in adipose tissue in lean and obese conditions. Both conventional and tissue-specific functions of adipose tissue macrophages (ATMs) in lean and obese adipose tissue are discussed and linked with metabolic and inflammatory changes that occur during the development of obesity. Furthermore, we will address various circulating and adipose tissue-derived triggers that may be involved in shaping the ATM phenotype and underlie ATM function in lean and obese conditions. Finally, we will highlight how these changes affect adipose tissue inflammation and may be targeted for therapeutic interventions to improve insulin sensitivity in obese individuals.